Construction of ZIF@electrospun cellulose nanofiber derived N doped metallic cobalt embedded carbon nanofiber composite as binder-free supercapacitance electrode. (1st September 2021) - Wu, Ying; Xu, Guilu; Zhang, Weilin; Song, Chi; Wang, Linjie; Fang, Xingyu; Xu, Lijie; Han, Shuguang; Cui, Juqing; Gan, Lu
Abstract: In this study, binder-free hybrid supercapacitance electrode based on N, Co co -doped porous carbon polyhedral encapsulated carbon nanofibers composites (N-Co/CNF) was prepared through pyrolyzing cobalt based zeolitic imidazolate frameworks (ZIF-67(Co)) incorporated electrospun cellulose nanofibers. With rational combination of the conductivity provided by cellulose derived CNF, promising porosity provided by CNF and ZIF-67(Co) derived porous carbon and uniformly dispersed metallic cobalt nanoparticles, the N-Co/CNF displayed excellent electrochemical properties. Specifically, the N-Co/CNF pyrolyzed at 800 °C possessed superior electrochemical performance in 1 M H2 SO4 electrolyte, including a specific capacitance of 433 F/g and 84% of the capacitance retention after 3000 consecutive charge-discharge cycles. This significantly exceeded the performance of cellulose derived CNF based pure carbonaceous electrode. Therefore, the present study provides a new view on the construction of high performance hybrid supercapacitance electrode which introduces renewable biomass resources like cellulose as both carbonaceous material precursors and conductive binders. Highlights: Hybrid supercapacitance electrode was prepared from MOFs incorporated cellulose nanofibers. Cellulose derived carbon nanofibers acted as supporting materials and conductive binder. The electrode pyrolyzed at 800 °C possessed optimal electrochemical performance. The electrode had a specific capacitance of 433 F/g and 84% retention after 3000 cycles.